Predictors of Dysphagia in Acute Pontine Infarction. Issue 5 (May 2017) - Lapa, Sriramya; Luger, Sebastian; Pfeilschifter, Waltraud; Henke, Christian; Wagner, Marlies; Foerch, Christian
Abstract : Background and Purpose—: Little is known about the frequency and the clinical characteristics of neurogenic dysphagia in pontine strokes. In this study, we sought to identify predictors for dysphagia in a cohort of patients with isolated pontine infarctions. Methods—: We included all patients admitted to our department between 2008 and 2014 having an acute (<48 hours after symptom onset) ischemic stroke in the pons, as documented by means of diffusion-weighted magnetic resonance imaging. Precise infarct localization was stratified according to established vascular territories. The presence of dysphagia was the primary end point of the study and was assessed by a Speech-Language Pathologist according to defined criteria. Results—: The study recruited 59 patients, 14 with and 45 without dysphagia. Median (interquartile range) stroke severity (in terms of National Institutes of Health Stroke Scale values) was higher in the dysphagic group as compared with patients without dysphagia (8.5 [6–12] versus 2 [1–5]; P <0.001). Infarct localization in the upper part of the pons (78.6% versus 33.3%; P =0.004) and in the anterolateral vascular territory (78.6% versus 31.1%; P =0.002) occurred more often in the dysphagic group. In a multivariate model, age, infarct volume, and National Institutes of Health Stroke Scale value were independent predictors of dysphagia. Conclusions—: Dysphagia occurs frequently in patients with isolated pontine infarctions. Clinical and imaging predictors of dysphagia may help to provide optimal screening, to prevent complications and to improve long-term prognosis. Abstract : Supplemental Digital Content is available in the text.